A taxonomic review of the brachiopod genus Australocoelia (Boucot & Gill, 1956) in the Devonian of Brazil - de Rezende, João Marcelo Pais; Da Costa Machado, Deusana Maria; de Oliveira Poncian, Luiza Corral Martins (Zootaxa, 2019)
The rhynchonellide brachiopod genus Australocoelia was widely distributed across the Southern Hemisphere in the Devonian with three species recognized; A. palmata, A. peruviana and A. polyspera. In Brazil, A. palmata was initially reported from the Ponta Grossa and São Domingos formations (Paraná Basin), later recorded from the western border of the Parnaíba Basin (Pimenteira Formation, State of Tocantins), and is now shown to occur on the eastern border of the same basin (Pimenteira Formation, State of Piauí). In this paper, we describe a fourth species from the Paraná Basin as Australocoelia boucoti n. sp. It differs from A. palmata and the other species of Australocoelia in features of ornamentation and interspace, in addition to paleoecological characteristics.